Description of the female morphology of the relict troglobiont millipede Cantabrodesmus lorioli Mauriès 1971 (Diplopoda, Polydesmida, Chelodesmidae), and new records in the deepest pit of Spain - Gilgado, José D.; Aguinaga, José A. Noriega; Enghoff, Henrik (Zootaxa, 2020)
The troglobiont millipede, Cantabrodesmus lorioli Mauriès, 1971, inhabits a few caves in a small region of Northern Spain. It is considered a relict species because of its geographical isolation compared to others in its family, and its to some extent uncertain systematic position. Cantabrodesmus lorioli has been placed in three different families, and now is considered a member of the Chelodesmidae, a family with only one other known native European representative. There are few records of this species, and almost nothing is known about its biology. The only available information on this species is the description of the male and a list of caves where it has been captured. In the present work, we provide the first description of the female morphology, illustrated by scanning electron microscopy, and a series of new records from caves in a region where it had never been captured before, including the deepest known pit in Spain, Torca del Porrón. The female morphology does not show many differences from that of the male, but several characters are discussed. All of the known information on the morphology of the species is used to discuss the implications for its biology and systematic position.